Implementing a Cold-Chain System for Nutritional Assessment in Rural Uganda; Field Experiences from FtF Nutrition Innovation Lab Cohort Study - Agaba Edgar; Shrestha Robin; Ghosh Shibani; K. Griffiths Jeffrey; Bashaasha Bernard (International Journal of Nutrition, 2018)
Objective: To elaborate on the procedures undertaken to establish blood draws and cold chain for nutrition assessments. Setting: A total of 5,044 birth cohort households were enrolled and assessed using household questionnaires, anthropometry, and blood sampling to assess nutritional issues and exposures to environmental contaminants. The challenge was to obtain, transport, process, store, and analyze tens of thousands of serum samples obtained in sites that were often difficult to reach. Approach: Before enrollment began, 24 healthcare facilities in the North and Southwest of Uganda were assessed for suitability as local nodes for processing and storage. Equipment needs included functional centrifuges, refrigeration, ice machines, and -20oC freezers. Other important physical infrastructure included the presence of backup power (generator or solar generated) in the event of electricity failure. Once samples were obtained, they were transported within 5 hours to the facility laboratories, where serum was separated and aliquoted into properly labelled storage tubes and then frozen. Relevant Changes: At community level, our team visited households or small group of household members close to their homes to reduce on travel time hence contributed to high retention rates. Our immediate testing for anemia and malaria results benefited enrollees and enhanced community acceptance. By using Village Health Teams (VHTs), we could accommodate household preferences for the timing of sample collection. Our engagement with phlebotomists transformed their role from a simple service into active team members. Lessons Learned: Our first lesson was that in our setting, the success of this nutrition biological sampling system required community engagement and acceptance. By combining an immediately actionable set of tests (for anemia and malaria), and visiting cohort households, we greatly enhanced the success of the system.
Keywords: nutrition assessment